2022
DOI: 10.4102/phcfm.v14i1.3147
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of intimate partner violence among men and women in Edo State, Southern Nigeria

Abstract: Background: Intimate partner violence (IPV) is a growing concern in Nigeria and globally. Although women are at greater risk of IPV, men are also affected, but this is less reported.Aim: This study sought to determine the prevalence and pattern of IPV among the respondents and to compare the pattern of IPV among the male and female respondents.Setting: The study was conducted in six towns (local government headquarters) across the three senatorial districts in Edo State, Southern Nigeria.Methods: The study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…, 2022 ). Another study in South-West Nigeria found an IPV prevalence of ∼38%, of which ∼80% of victims were women ( Oseni et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022 ). Another study in South-West Nigeria found an IPV prevalence of ∼38%, of which ∼80% of victims were women ( Oseni et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the lower prevalence of IPV among men ‘establishes the culture of silence; that is, IPV is more likely to be under-reported in men’ ( Oseni et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are similarities among the factors contributing to low incidence in different parts of the country, certain regions show peculiar features; for instance, in the south-south region of Nigeria, the low incidence was attributed to the fact that the people do not consider psychological violence as a form of violence-unlike the northern part that view violence as physical attacks, psychological aggression and sexual coercion-the lack of routine screening for domestic violence, clinicians discomfort and misconception are other factors in the regions. 8 In the south-eastern part of the country, factors like financial inequality favouring women, powerful in-laws, educated women and couples within the same age group were responsible for low incidence report. These findings are similar to other parts of the country.…”
Section: Discussionmentioning
confidence: 99%
“…5 Both men and women are affected by IPV but most of the cases are perpetrated by men against women. 6 Worldwide, around 30% of women aged 15–49 years have experienced physical and/or sexual violence by their intimate partner at least once in their lifetime. 2 7 IPV varies significantly across regions.…”
Section: Introductionmentioning
confidence: 99%